Gamification Approach in Teaching and Learning - Jaffar, Muhammad Ikmal (Journal of Computing Technologies and Creative Content, 2019)
Abstract: Gamification is outlined as applying a typical gameplay option to other areas of interaction, particularly in the learning process. However, there is still a lack of awareness among educators about the technique of gamification that is acceptable to be implemented. A literature review was conducted to close the identified gap associated with gamification in online environments. Three main categories were identified to study the effect of the gamification approach in teaching and learning which are student satisfaction, learning outcomes and participation. This research is conducted to identify the impact of gamification elements on a student’s motivation and learning process.